2014
DOI: 10.1016/j.actbio.2013.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Degradation in the dentin–composite interface subjected to multi-species biofilm challenges

Abstract: Oral biofilms can degrade the components in dental resin-based composite restorations, thus compromising marginal integrity and leading to secondary caries. In this study, we investigated the mechanical integrity of the dentin-composite interface challenged with multi-species oral biofilms. While most studies used single-species biofilms, we used a more realistic, diverse biofilm model produced directly from plaques collected from donors with a history of early childhood caries. Dentin–composite disks were mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 43 publications
(49 reference statements)
7
114
1
8
Order By: Relevance
“…Kermanshahi et al [101] also demonstrated that the synergistic activity of salivary esterases, CE and PCE, may result in degradation of Bis-GMA-based resins, extensive enough to allow bacterial leakage at the interface. Recently, it was shown that bacteria from dental plaque, for example Streptococcus mutans, with a similar esterase activity as in saliva, may also partake in the interfacial degradation [102,103].…”
Section: Biodegradation Of the Interfacementioning
confidence: 99%
“…Kermanshahi et al [101] also demonstrated that the synergistic activity of salivary esterases, CE and PCE, may result in degradation of Bis-GMA-based resins, extensive enough to allow bacterial leakage at the interface. Recently, it was shown that bacteria from dental plaque, for example Streptococcus mutans, with a similar esterase activity as in saliva, may also partake in the interfacial degradation [102,103].…”
Section: Biodegradation Of the Interfacementioning
confidence: 99%
“…In total, 60 dentin-composite disc samples were prepared using bovine incisors as described previously [17,23,27]. Root sections from below the cementum-enamel junction with a root canal diameter less than 2 mm and an outer diameter larger than 5 mm were used.…”
Section: Sample Preparationmentioning
confidence: 99%
“…While it should be possible to engineer repetitive cycles of pH, solute-solvent combinations, thermal cycling and mechanical loading that generate compressive, tensile and shear stress, other key parameters are the patient's salivary composition and amounts, shifting occlusal loads, dietary habits and oral cleanliness. Emerging research can be interpreted as if even the individual's intra-oral bacterial profile may play a role in the biodegradation of some polymers [43], which is a factor that is very difficult to simulate in a laboratory model [44].…”
Section: Restorative Materials and The Tooth-restoration Interfacementioning
confidence: 99%